Comparison of theoretical total electron content (TEC) during disturbance - Roziana, Binti Che Musa (Universiti Malaysia Sarawak, UNIMAS, 2010)
The ionosphere layer is very important to the communication system and the Total Electron Content (TEC) plays an important role in the study of ionospheric behavior. This project involves the comparison of TEC simulated using theoretical models and real data during the disturbances due to geomagnetic quiet and the disturbed day at Equatorial region and Middle Latitude Region. Prediction of TEC is carried out using two theoretical models which are International Reference Ionosphere 2001(IRI-2001) PC using window version and NeQuick using the sample driver’s slQu.exe. Both theoretical models are the standard model available from the International Telecommunication Union-Radio Sector (ITU-R). The real data in the form of IONospheric map Exchange (IONEX) from the Centre for Atmosphere Determination (CODE) is used for comparison. Results show that the TEC values for Equatorial Region is higher than the Middle Latitude region. It is recommended that for undergo improvement, both theoretical models (IRI2001 and NeQuick) should include ionospheric disturbance for more reliable TEC calculation.